PERENCANAAN JALUR SEPEDA berdasarkan persepsi dan preferensi wisatawan bersepeda DI PANTAI SANUR BALI - Komang Wirawan (Sekolah Tinggi Pariwisata Mataram, 2021)
Tourists as part of driving the economy in Bali are decreasing in number along with the spread of positive cases of Covid 19 in 2020. This is in contrast to cycling tourists who are increasingly visiting the island of Bali from day to day. The Sanur Tourism Destination is no exception, which remains busy during the pandemic. Infrastructure is needed to support cycling tourism activities, one of which is a bicycle path that makes it easier for tourists to explore destinations. Bicycle lanes as part of human movement traffic infrastructure are increasingly being considered in realizing the city as a center of friendly and green activities today. The purpose of this study was to determine the preferences and perceptions of cycling tourists about bicycle paths in Sanur and what kind of planning is in accordance with the needs and desires of cycling tourists. The method used in this research includes distributing questionnaires, observation, literature review of secondary data collection to related stakeholders. The analysis includes qualitative analysis and qualitative descriptive. The results of this study are 1) The preferences of tourists in cycling tend to maintain health. Tourists who dominate during the pandemic are local tourists and domestic tourists replacing foreign tourists who were dominant before the pandemic. 2) The perception of supporting facilities for cycling tourism consists of facilities of good quality and quantity such as bicycle parking, bicycle rental, seating, food and beverage vendors, facilities that need to be improved, such as drinking water taps, public toilets, signposts and information. and facilities that need to be added, such as road dividers between pedestrians and bicyclists, portals. 3) Planning a bicycle path in the future from the side of cycling tourists needs to pay attention to comfort and safety in terms of cyclists and pedestrians on pedestrians.